2020
DOI: 10.3389/fgene.2020.00998
|View full text |Cite
|
Sign up to set email alerts
|

The Crosstalk Between Epigenetic Mechanisms and Alternative RNA Processing Regulation

Abstract: As a co-transcriptional process, RNA processing, including alternative splicing and alternative polyadenylation, is crucial for the generation of multiple mRNA isoforms. RNA processing mechanisms are widespread across all higher eukaryotes and play critical roles in cell differentiation, organ development and disease response. Recently, significant progresses have been made in understanding the mechanism of RNA processing. RNA processing is regulated by transacting factors such as splicing factors, RNA-binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 101 publications
0
46
0
2
Order By: Relevance
“…Methylation is known to regulate splicing [54][55][56][57], but alternative isoforms of DNA methyltransferases genes or genes regulating chromatin conformation or methylation can also modulate methylation profiles [32]. Although mutations in genes required for splicing and methylation commonly occur in leukemia, and a mutation in a splicing factor (SRSF2) has been shown to impact methylation in acute myeloid leukaemia [58], the interaction of these two processes has not been described in CLL patients carrying SF3B1 mut .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylation is known to regulate splicing [54][55][56][57], but alternative isoforms of DNA methyltransferases genes or genes regulating chromatin conformation or methylation can also modulate methylation profiles [32]. Although mutations in genes required for splicing and methylation commonly occur in leukemia, and a mutation in a splicing factor (SRSF2) has been shown to impact methylation in acute myeloid leukaemia [58], the interaction of these two processes has not been described in CLL patients carrying SF3B1 mut .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, all three DNA methyltransferases (DNMTs) are subjected to alternative splicing [29][30][31] and, therefore, mutations in splicing factors can potentially lead to changes in the methylation profiles, either directly by affecting the splicing of the DNA methyltransferases and DNA demethylases genes, or by alternatively spliced isoforms of the chromatin and methylation regulators, such as non-coding RNAs [32]. Thus, to achieve a better understanding on the methylome changes in CLL patients and how they might be connected to mutations in SF3B1, we compared genome-wide methylation profiles of CLL patients with (SF3B1 mut ) and without (SF3B1 WT ) SF3B1 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…This association of environment‐induced alternative splicing activity with regulators offers an elegant means of rapidly deploying phenotypic plasticity to a system under stress. It is perhaps not surprising, then, that gene‐associated DNA methylation repatterning occurs within gene networks that align with stress response pathways and phenotype changes (Yang et al ., 2020; Kundariya et al ., 2020); subtle methylation changes may be sufficient to adjust or respond to local splicing changes that relax phenotypic constraints (Zhang et al ., 2020).…”
Section: Alternative Rna Splicing As a Nuclear Response To Organellar Signalingmentioning
confidence: 99%
“…Altogether our results and other published data demonstrate that SLU7 and DNMT1 control gene expression at different levels, but both play essential roles maintaining genome integrity, cell proliferation and cell survival. Recent results have demonstrated a narrow connection and interplay between the different mechanisms implicated in the regulation of gene expression including DNA methylation and alternative splicing ( 20 , 21 ). Having demonstrated that SLU7 regulates both splicing and transcription, we decided to investigate whether SLU7 also regulates DNA methylation, representing a new hub integrating different levels of gene expression regulation.…”
Section: Introductionmentioning
confidence: 99%